2019
DOI: 10.1177/2192568219830323
|View full text |Cite
|
Sign up to set email alerts
|

Essential Concepts for the Management of Metastatic Spine Disease: What the Surgeon Should Know and Practice

Abstract: Study Design: Literature review. Objective: To provide an overview of the recent advances in spinal oncology, emphasizing the key role of the surgeon in the treatment of patients with spinal metastatic tumors. Methods: Literature review. Results: Therapeutic advances led to longer survival times among cancer patients, placing significant emphasis on durable local control, optimization of quality of life, and daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 110 publications
(142 reference statements)
1
46
0
1
Order By: Relevance
“…Many studies analyzed effectiveness of cEBRT both as primary and adjuvant treatment for MESCC. Historically, cERBT with palliative intent (30 Gy in 10 fractions, 20 Gy in 5 fractions or 8 Gy in one fraction) have been considered the main treatment options for spinal metastases [20] . In a recent review, Barzilai et al underlined the wide range of response duration and recurrence rate after adjuvant cERBT and its strong dependency from tumor histology of primary tumor, with poorly responses in radioresistant tumors [36] , [42] , [51] .…”
Section: Evolutions In Radiotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies analyzed effectiveness of cEBRT both as primary and adjuvant treatment for MESCC. Historically, cERBT with palliative intent (30 Gy in 10 fractions, 20 Gy in 5 fractions or 8 Gy in one fraction) have been considered the main treatment options for spinal metastases [20] . In a recent review, Barzilai et al underlined the wide range of response duration and recurrence rate after adjuvant cERBT and its strong dependency from tumor histology of primary tumor, with poorly responses in radioresistant tumors [36] , [42] , [51] .…”
Section: Evolutions In Radiotherapymentioning
confidence: 99%
“…Considering the systemic nature of MESCC, surgical treatment plays a functional role in preserving or restoring neurological status and spinal stability [6] , [16] , [20] . With the introduction of ablative radiation treatment (SRS or SBRT) in the new paradigms of treatment [16] , surgery for decompression in MESCC has evolved, shifting from aggressive cytoreduction, in order to obtain neurological outcomes improvement and better LC, towards the modern idea of “separation surgery”(SS) [7] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With technological advancement, MISS for spine metastasis has become feasible, and thus has been considered as a new treatment option over traditional open surgery [ 38 ]. Several studies have reported equivalent functional outcomes and faster recovery with reduced morbidity, such as blood loss and surgical site infection [ 3 , 39 - 42 ].…”
Section: Minimally Invasive Spine Surgery For Complex Spine Pathologymentioning
confidence: 99%
“…In 2019, Barzilai et al [ 39 ] suggested a treatment algorithm for spine metastasis, which consisted of following: patient evaluation using the health-related quality of life questionnaire; cancer-related spinal instability; epidural spinal cord compression; tumor biology; primary or adjuvant radiotherapy; and spinal surgeries such as separation surgery, minimal access surgery, and stabilization. Given the careful patient selection, MISS for spine metastasis significantly reduces surgery-related morbidity and improves patients’ quality of life compared with traditional open surgery.…”
Section: Minimally Invasive Spine Surgery For Complex Spine Pathologymentioning
confidence: 99%